“Vital Industry” and Women's Ventures: Conceptualizing Gender in Twentieth Century Business History - Peiss, Kathy (Business History Review, 1998)
In 1935 Fortune magazine published a series of articles on “Women in Business” whose true subject was the absence of women in business. Published anonymously but written by Archibald MacLeish, the articles distinguished between the relatively few women in “general business” or “business proper” and the greater number “engaged in the business exploitation of femininity.” MacLeish asserted that this was “not merely an arbitrary” distinction, for businesses dominated by men were “vital industries.” Vital is a significant adjective from a man known to choose his words carefully, with its connotations of fundamental, indispensable, robust, animate, and, not least, virile. Unlike men's efforts in business, said MacLeish, “feminine success in the exploitation of women proves nothing but the fact that women are by nature feminine.” That is, women's ventures in cosmetology, fashion and styling, department store buying, advertising to women, and the women's press resulted from a state of being, not a will to action. As MacLeish put it, “Elizabeth Arden is not a potential Henry Ford. She is Elizabeth Arden. It is a career in itself but it is not a career in industry.”
Keywords: Business History and gender